On the temporal values of situation-participant NP referents mapped from Bulgarian perfects with aorist and imperfect participles - Kabakčiev, Krasimir (East European Journal of Psycholinguistics, 2023)
This paper deals with Bulgarian съм+-л (‘be’+past active participle) perfect verb forms with aorist and imperfect participles, the distinction between these two participles being a phenomenon found only in Bulgarian among the Slavic languages and generally absent in other languages too. According to the majority of Bulgarianists today, imperfect participles are not used in perfect verb forms. However, this thesis is considered here a fully defective one for several reasons, among which: no argumentation has ever been provided to explain the thesis in essence – for example, in its possible connection to the aspectual values encoded in aorist and imperfect participles, or to the general characteristics of съм+-л forms. These forms can effectuate many TAM meanings – not only of “a standard perfect” but also modal ones such as inferentiality, renarration, dubitativity. Following the author’s definition of aspect as an all-pervading and perpetual process of mapping temporal features between verbal and nominal referents, specific uses of imperfect and aorist participles in sentences with perfect verb forms are analyzed, and the impact the relevant participle (imperfect or aorist) exerts on the temporal values of situation-participant NP-referents is analyzed and identified. The major generalization is that the never-ending process of mapping temporal features from verbs to nominals (NPs) that occurs in verbal-aspect languages (Slavic, Greek, Georgian), and vice versa, from nominals (NPs) to verbs that occur in compositional-aspect languages (Dutch, English, Finnish) is a crucial psychophysiological mechanism ingrained in peoples’ heads and conditioning the development of grammatical structures of languages. Intriguingly, this process is linguistically fully identifiable at the speaker-hearer interaction level but remains entirely beyond the awareness of the ordinary native speaker. Author: Krasimir Kabakčiev 0000-0002-5529-0872 kkabakciev@atiner.gr